Pengaruh Kualitas Layanan, Nilai Nasabah, Kepercayaan dan Kepuasan Terhadap Loyalitas Nasabah Pengguna Layanan Mobile Banking Syariah - Astuti, Yulia Widi; Agriyanto, Ratno; Turmudzi, Ahmad (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2020)
This study analyzes the effect of service quality, customer value, trust and satisfaction on customer loyalty at Bank Syariah Mandiri. The problem in this research is: how to increase customer loyalty of mobile banking service users at BSM. This study used 100 respondents using mobile banking services at BSM in the city of Semarang. Data analysis using SEM with the Smart PLS 3 computer program. The results showed that, among other things, service quality had a positive and insignificant effect on loyalty. Customer value has a positive and significant effect on loyalty. The effect of trust on customer loyalty has a positive and insignificant effect. Meanwhile, satisfaction has a positive and significant effect on loyalty.